Chemical Characteristics of Low-Calories Hard Candy Contains Trigona’s Honey and Patchouli Oil as Functional Confectionery - Juliani Juliani; Irmayanti Irmayati (Universitas Serambi Mekkah, 2022)
Functional confectionery is a consumption trend driven by consumers across generations that demands convenient nutrition. Functional candy contains healthful ingredients such as trigona’s honey and essential oil, including Patchouli Oil. On the other hand, the high sugar content in candy can cause obesity, diabetes, and dental carries; hence, Isomalt and Trigona Honey were used in this study to reduce calorie intake in the hard candy. This research thus aimed to determine the effect of different low-calorie formulas and different concentrations of PO added to chemical characteristic functional hard candy. The data were analyzed descriptively and compared to the Indonesian Standard of Hard Candy (SNI 3547.1:2008). The low-calorie formula (G1, G2, and G3) and the concentration of patchouli oil (PO1, PO2, PO3, and PO4) determined the water content, ash content, and total dissolved solids. The result shows that the low-calories hard candy containing Trigonas Honey and Patchouli Oil has a total of dissolved solids of 7,4-13,8 °Brix, with a water content of 0,65-3,21% (SNI max 3,5%), and ash content of 0.02 - 0.11% (SNI max 2,0%). It can be concluded that the hard candy that containing trigona’s honey and patchouli oil has the chemical characteristics as requirements of SNI 3547.1:2008, which has potential as a new functional candy. Keywords: Essential Oil, Isomalt, Low-Calories, Functional Food, Honey